?????evauate?????????
![evauate class=](https://us-static.z-dn.net/files/d29/92020677ee53c96a643dd6bdfeeca33e.png)
Answer:
2
Step-by-step explanation:
Substitute a = - 6 into the expression, that is
a² + 7a + 8
= (- 6)² + 7(- 6) + 8 = 36 - 42 + 8 = - 6 + 8 = 2
Answer:
2
Step-by-step explanation:
[tex] {a}^{2} + 7a + 8[/tex]
Substitute
[tex]a = - 6[/tex]
in the above equation to get:
[tex] {( - 6)}^{2} + 7( - 6) + 8[/tex]
Simplify:
[tex]36 + ( - 42) + 8[/tex]
[tex]36 - 42 + 8[/tex]
[tex] - 6 + 8[/tex]
[tex]2[/tex]